The protective effect of Curcuma longa on male infertility induced by thioacetamide. (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aimed to investigate the impact of thioacetamide (TAA) on the structure and function of the testes and assess the therapeutic effects of Curcuma longa (Cl) against TAA-induced toxicity in rats. Materials and Methods: Thirty-two male albino rats weighing 180–200 gm and aged 11–12 weeks were randomly separated into four groups. The control group was given normal saline, the Cl group was orally administered Cl (500 mg/kg/day), the TAA group received intraperitoneal TAA (200 mg/kg body weight, three times/week), and the Cl with TAA group received Cl orally two hours before TAA administration. After 8 weeks, all rats were anesthetized, and body and testis weights were recorded. Morphological and histological assessments as well as biochemical analyses were conducted. Results: The study revealed a significant decrease in both body and testis weights in the TAA group, accompanied by a substantial increase in luteinizing hormone (LH), follicle-stimulating hormone (FSH), and malondialdehyde (MDA) levels. Testosterone (T) and glutathione (GSH) were significantly decreased in the TAA-treated group compared to the control. Conversely, the Cl-treated group exhibited a substantial decrease in LH, FSH, and MDA levels while showing a significant increase in T and GSH. Conclusion: Cl has been found to have a potential therapeutic role in mitigating TAA-induced testicular damage by acting as an antioxidant. This is supported by a significant decrease in oxidative stress markers and supporting hormonal levels. Further research is needed to understand the underlying mechanisms and explore the clinical applicability of Cl in preventing and treating testicular toxicity. J. Adv. Vet. Anim. Res., 11(3): 762-771, September 2024http://doi.org/10.5455/javar.2024.k828